The Effect of Pancasila Student Profile on the Numerical Literacy Ability of Junior High School Students - Setiyani Setiyani; S.B. Waluya; Y.L. Sukestiyarno; Adi Nur Cahyono; DPD Santi (Universitas Negeri Semarang, 2022)
This study aims to see how the influence of the profile of Pancasila students in seventh grade junior high school students on numeracy literacy skills related to mathematical literacy. The samples in this study were students from SMP Negeri 2 and SMP Negeri 4 Cirebon City class VII totaling 56 students. The type of research used is a quantitative methodology. Data analysis in this study used descriptive statistics and inferential statistics with Pearson correlation analysis. This study uses the independent variable, namely the ability of numeracy literacy and the dependent variable, namely the character profile of Pancasila students. For data collection using questionnaires and test questions. The questionnaire contains 18 statements with 6 indicators of the Pancasila student profile and 6 test questions with 3 indicators of numeracy literacy. The results of this study indicate that the ability of numeracy literacy has a positive effect on the character profile of Pancasila students